Efficacy of daclatasvir plus asunaprevir in patients with hepatitis C virus infection undergoing and not undergoing hemodialysis. Issue 9 (17th May 2018) - Fujii, Hideki; Kimura, Hiroyuki; Kurosaki, Masayuki; Hasebe, Chitomi; Akahane, Takehiro; Yagisawa, Hitoshi; Kato, Keizo; Yoshida, Hideo; Itakura, Jun; Sakita, Shinya; Satou, Takashi; Okada, Kazuhiko; et al.
Abstract : Aim: To evaluate the virologic responses and clinical course of daclatasvir plus asunaprevir treatment in non‐hemodialysis (non‐HD) and hemodialysis (HD) patients infected with genotype 1 hepatitis C virus (HCV). Methods: A total of 1113 non‐HD patients and 67 HD patients were assessed. To evaluate pretreatment factors contributing to sustained virological response at 12 weeks (SVR12), univariate and multivariate analyses were carried out. To adjust for differences in patient background, propensity score matching was undertaken. Results: The overall SVR12 rates were 91.6% in non‐HD patients and 95.5% in HD patients. Compared with non‐HD patients, HD patients were younger, were more likely to be male, were less likely to have received interferon‐based pretreatment, had a lower viral load, and had lower levels of alanine transaminase, hemoglobin, and α‐fetoprotein. Multivariate analysis revealed that viral load, α‐fetoprotein, L31 substitution negative, and Y93 substitution negative were independent predictive factors for SVR12 in non‐HD patients. The proportion of patients with undetectable HCV‐RNA during the initial 4 weeks was significantly higher in HD patients than in non‐HD patients. The SVR12 rate was clearly higher in HD patients than in non‐HD patients, although the difference was not statistically significant. After propensity score matching to adjust for viral load, α‐fetoprotein, L31 substitution, and Y93 substitution, these trends disappeared. Conclusions: For treatment of HCV genotype 1 infection, daclatasvir plus asunaprevir is useful not only in non‐HD patients but also in HD patients. Viral load, α‐fetoprotein levels, L31 substitution, and Y93 substitution influence treatment course and outcome.